Identification of the competent superior as an effect of implementation of the can. 698 CIC/83 - MICHOWICZ, PRZEMYSŁAW (Prawo Kanoniczne, 2017)
The paper proposes the constructive reflection on the possible procedural configuration inherent in the proceedings of dismissal, in particular consideration of the hypothesis exposed in the can. 698. The Legislator assures to the accused religious the right to communicate and to offer his proper defenses directly to the supreme Moderator of the Institute. The Author tries to indicate the competent religious Authorities in order to receive the legal claim from the religious, accused for having committed crimes or illegal acts specified in the can. 695 and can. 696. Using the legal instruments like appeal and call to the proper jurisdiction – foreseen in the Code of canon law - helped to verify whether and how the exercise of the right to communicate with the supreme Moderator may be equivalent to the mentioned procedural instruments. Unfortunately, the conclusions we reached do not allow assigning any nomen iuris to the hypothesis in which the demand submitted by the accused religious could be accept by the highest Authority of his proper Institute. Eventually, the Author proposed the possible solution of the specified doctrinal problem. It is likely that the supreme Moderator, having determined his exclusive competence in order to lead the entire case and having communicated it to the Superior in loco, could have a burden to supplement the evidences and finalize the cause. It was also considered inopportune or inadvisable to accept the demand forwarded by the religious simultaneously with the notification of the arguments against him. It can’t be excluded another hypothesis according to which the same supreme Moderator will end the dispute using the extra canonical solutions.